KARDIOCHIRURGIA DOROSŁYCHInfluence of preoperative diabetes compensation on complications after cardiac surgery - Biskupski, Andrzej; Kowalik, Bogdan; Sielicki, Piotr; Mokrzycki, Krzysztof; Żych, Andrzej; Zegan, Małgorzata; Żukowski, Maciej; Brykczyński, Mirosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: Diabetes mellitus is one of the most common civilization-related diseases of the 21st century. It appears in nearly 1/3 of patients operated on in cardiac surgery departments. Objectives: The aim of the study was to assess frequency of complications after cardiac surgery according to the level of preoperative diabetes compensation. Material and methods: The study was conducted on 130 patients operated on from December 2008 to September 2009. Patients with HbA1c level higher than 7%, suffering from uncompensated diabetes, were included in the study group. Patients with HbA1c level lower than 7% with compensated diabetes formed a control group. Mortality and frequency of complications after cardiac operations in both groups were assessed and compared. Results: Risk of perioperative mortality according to the EuroSCORE scale was comparable in both groups (5.32% vs. 5.66%). In the control group (68 pts, 52%) there were no deaths, cardiac events appeared in 16 pts (23.5%), cerebrovascular accidents in 6 pts (8.8%), renal failure in 9 pts (13.2%), respiratory insufficiency in 1 patient (1.5%), and no wound infection was noticed. In the study group (62 patients, 48%) 3 deaths (4.8%) were noticed, cardiac events appeared in 24 pts (38.7%), cerebrovascular accidents in 11 pts (16.2%), renal failure in 8 pts (12.9%), respiratory insufficiency in 5 pts (8.1%) and wound infections were noted in 2 patients (3.2%). Conclusions: 1. Nearly half of patients with diabetes diagnosed preoperatively were operated on in uncompensated status. 2. Preoperative compensation of diabetes significantly reduces postoperative complications and mortality. 3. Preoperative examination of HbA1c is a good predictor of postoperative complications after cardiac surgery